Examining Public Library Collaborative Partnerships with School Makerspaces and "Making Programmes". Issue 6 (18th August 2022) - Yuen, Krista; Liew, Chern Li
Abstract: Scholarly investigations into the extent and nature of schools and public libraries collaborating in the "maker/making" space are scant. This research sets out to address this knowledge gap, by investigating the perspectives of public libraries' staff: How public libraries and schools have worked together on makerspaces and "making" programmes, the motivations for and the nature of collaborations, and challenges that need addressing for successful collaborations, and their perceived outcomes of such collaborations. This study shows how through collaborating with schools, public libraries can make meaningful contributions to social and digital inclusion in their communities, fulfilling their roles as social institutions. Our findings highlight the importance of contextual flexibility to be considered in such collaborations, with partnering organizations negotiating a suitable model for working together. The roles and contributions of each party involved could be considered across spectrums of engagement, planning, resource-sharing, and activities, depending on the contextual needs, priorities, and requirements of the partnering institutions. We discuss how these can be achieved through dialogic communication for sustained partnerships.